Ontogeny of the catfish pectoral‐fin spine (Teleostei: Siluriformes). (22nd January 2019) - Kubicek, Kole M.; Britz, Ralf; Conway, Kevin W.
Abstract: The characteristic and morphologically variable pectoral‐fin spine of catfishes (order Siluriformes) has been well‐investigated based on later developmental stages (juveniles and adults) but information on the earliest life stages are lacking. Here, we document the ontogeny of pectoral‐fin spines in four siluroid ( Ictalurus punctatus, Noturus gyrinus, Silurus glanis and Akysis vespa ) and two loricarioid catfishes ( Corydoras panda and Ancistrus sp.). To further our understanding of pectoral‐fin spine development, we also examined adult and juvenile specimens representing 41 of the currently 43 recognized families of catfishes. Development of the pectoral‐fin spine is similar in all catfishes and resembles the development of a typical soft fin ray. Fusion between hemitrichia of the anteriormost lepidotrichium occurs proximally first, forming the spine proper, with growth of the spine occurring through the subsequent fusion of developing distal hemitrichial segments that comprise the spurious ray. The variation of pectoral‐fin spine morphology observed is largely attributed to the presence/absence of five traits, which either develop as part of the hemitrichial segments that are added to the distal tip of the spine during growth (distal rami, anterior/posterior serrae) or develop independent of these segments (denticuli and odontodes). Abstract : We provide an ontogenetic perspective on the morphologically diverse pectoral‐fin spine of the catfishes (Siluriformes). Development of the spine is highly conserved across the different groups of siluriformes and variation in adult morphology is largely attributed to the presence/absence of five traits (distal rami, anterior and posterior serrae, denticuli and odontodes).